2017
DOI: 10.1111/ggi.13171
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with mild cognitive impairment among Chinese older adults with depression

Abstract: Aim: Depression and mild cognitive impairment (MCI) are common among older adults. Most of the existing studies were carried out in developed countries, and evidence from developing countries are lacking. In the present study, using a national sample, we aimed to describe the prevalence of MCI and its associated factors among Chinese older adults with depression. Results:The results showed that the prevalence of geriatric depression was 15.9%, and 36.4% of those with depression had MCI. Geriatric depression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…High levels of heterogeneity were found (I 2 > 75%) across the 41 included studies. Of the 38 studies reporting MCI prevalence, three [ 39 , 45 , 59 ] showed significant deviation from the others both in sensitivity tests and visual funnel asymmetry. The Egger’s and Begg’s tests also revealed significant publication bias in the studies ( β = 0.002, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…High levels of heterogeneity were found (I 2 > 75%) across the 41 included studies. Of the 38 studies reporting MCI prevalence, three [ 39 , 45 , 59 ] showed significant deviation from the others both in sensitivity tests and visual funnel asymmetry. The Egger’s and Begg’s tests also revealed significant publication bias in the studies ( β = 0.002, p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…", yes or no). In addition, we collected information on medical history, including self-reported diagnoses of diabetes (yes or no), heart disease (yes or no), and respiratory disease (yes or no), hypertension (yes or no based on self-report of a diagnosis by a doctor or physician, or on measured systolic blood pressure ≥140 mmHg or diastolic blood pressure ≥90 mmHg), and disability in activities of daily living (ADL) (yes or no) (Han et al 2019;Li et al 2018;Tervo et al 2004). Blood pressure was measured using a mercury sphygmomanometer after 5 min of rest, and the average value of the two measurements was used for analysis.…”
Section: Covariatesmentioning
confidence: 99%
“…These previous studies have concluded that residents who were younger, were male, had impaired cognitive function, were widowed or had never married, had poor physical function, were illiterate (did not go to any school and did not know how to read or write), experienced pain, experienced loneliness, had difficulty swallowing, had poor perceived health status, lived in an intermediate care facility, or had a shorter length of residency were more prone to have depressive symptoms or depression. Because the evidence shows that cognitive impairment is associated with depressive symptoms or depression (Li et al, ), healthcare professionals might easily overlook the mental health of residents with intact cognitive function.…”
Section: Introductionmentioning
confidence: 99%